2009
DOI: 10.1097/ico.0b013e318196703a
|View full text |Cite
|
Sign up to set email alerts
|

Optical Image Quality and Visual Performance for Patients With Keratitis

Abstract: Devices to measure optical image quality and the CSF enable the characterization of the optical quality and visual performance in patients with keratitis, showing a significant decline in optical quality and visual performance during keratitis and an improvement after the resolution of the pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 14 publications
2
27
0
8
Order By: Relevance
“…In the case of healthy fellow eyes, the mean was 0.29 ± 0.14, indicating a significantly lower value ( p = 0.008) in the Strehl ratio for keratitis eyes, and therefore, a stronger influence of aberrations, retinal reflection, and intraocular scattering, as some works have shown. 10,11 In accordance with previous research, 10 the same tendency was found in ARMD patients where the average Strehl ratio was 0.10 ± 0.03 for pathological eyes (ranging from 0.056 to 0.156) and 0.18 ± 0.05 for contralateral healthy eyes, the differences being significantly lower for the diseased eyes (p = 0.012). Analyzing the averages, we found the mean value for the Strehl ratio to be significantly lower in keratitis and ARMD eyes compared to the mean for the healthy fellow eyes.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the case of healthy fellow eyes, the mean was 0.29 ± 0.14, indicating a significantly lower value ( p = 0.008) in the Strehl ratio for keratitis eyes, and therefore, a stronger influence of aberrations, retinal reflection, and intraocular scattering, as some works have shown. 10,11 In accordance with previous research, 10 the same tendency was found in ARMD patients where the average Strehl ratio was 0.10 ± 0.03 for pathological eyes (ranging from 0.056 to 0.156) and 0.18 ± 0.05 for contralateral healthy eyes, the differences being significantly lower for the diseased eyes (p = 0.012). Analyzing the averages, we found the mean value for the Strehl ratio to be significantly lower in keratitis and ARMD eyes compared to the mean for the healthy fellow eyes.…”
Section: Resultssupporting
confidence: 91%
“…8,9 Patients with keratitis have diminished optical quality and a deteriorated visual performance. 10,11 This study included 15 patients with unilateral keratitis with a mean age of 34.2 ± 11.6 years (standard deviation) and a range of 14-62 years. Patients with a Snellen visual acuity lower than 6/15 or any other ocular diseases except for keratitis were excluded from the study.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A version of the DP device (OQAS-II, Visiometrics SL, Tarrasa, Spain) has been used in clinical environments to measure the retinal image quality under different conditions [6][7][8][9][10]. Although this instrument has a clear clinical potential, it cannot provide a direct correlation between the subject's visual performance and the retinal image quality estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the potential of this technique in basic research (Artal et al, 1995a;Williams et al, 1994Williams et al, , 1996 and in its application to ophthalmology, optometry, and ophthalmic optics testing. In particular, it has been used to assess retinal image quality in patients with keratitis (Jiménez et al, 2009) and patients undergoing refractive surgery, such as LASIK (Vilaseca et al, 2009a;Vilaseca et al, 2010b) and intraocular lens implants (Vilaseca et al, 2009a;Alió et al, 2005;Fernández-Vega et al, 2009;Artal et al, 1995b). This technique has also been used to evaluate presbyopia after photorefractive keratectomy (Artola et al, 2006), to study retinal image quality in contact lens wearers (Torrents at al., 1997), and to analyse in vitro optical quality of foldable monofocal intraocular lenses (Vilaseca et al, 2009b).…”
Section: Clinical Assessment Of Retinal Image Quality In Eyes With Asmentioning
confidence: 99%